Rubberwood-Polymer composites based on diallyl phthalate and methyl methacrylate - Rozman H D; Abusamah A; Kumar R N (Journal of Applied Polymer Science, 1995)
Wood-polymer composites(WPC) of rubberwood(Hevea brasiliensis), were prepared by impregnating the wood with methyl methacrylate(MMA), and the combinations of MMA and diallyl phthalate(MMA/DAP). Polymerization was carried out by catalyst heat treatment. Impregnated samples showed significant improvements in compressive and impact strengths, hardness, and dimensional stability (towars water) over that of the untreated rubberwood.
Keywords: Rubberwood